Dropouts, Stopouts, Optouts at Del Mar College Spring 1991. Report of a Joint Research Project / Jo Ann I. Luckie and L. Adrianne Bonham. - Luckie, Jo Ann I. (Distributed by ERIC Clearinghouse, 1991)
A research project investigated 2,313 persons who attended Del Mar College (Texas) during fall 1990 but did not enroll for spring 1991. Four sets of data were collected: (1) limited demographic information on the total student body; (2) demographic information drawn from school records to describe all nonreturnees; (3) demographic information describing 642 nonreturnees who were unreachable; and (4) demographic information plus telephone survey information from 399 nonreturnees. From a student body of 10,538, 2,313 were nonreturnees. Males and White non-Hispanice were overrepresented among nonreturnees. Within the whole group of nonreturnees, the numbers of female Hispanics and Whites and male Hispanics and Whites were about the same. Besides the 17 percent who withdrew from all classes, 23 percent of nonreturnees received all F grades; however, almost one-third maintained A or B averages. Almost 18 percent of the unreachables had transferred or graduated; almost 24 percent had relocated. A total of 113 persons should not have been on the nonreturnee list among the 1,041 studied; 304 were estimated to be dropouts; 82 indicated they were optouts; 303 indicated that they were stopouts; and 239 could not be classified. Reasons for not returning had to do with life circumstances in general and not with school in particular. Suggestions were made for further research and for action to be taken by Del Mar College. (Additional data and the questionnaire are appended.) (YLB)